American studies, Capital and the Gothic - Grgas-Mufa, Stipe (2014)
The author argues that American Studies have to recognize the centrality of the gothic genre in the readings of US experience particularly if those readings address the issue of capital. In his analysis he rehearses the presence of the gothic in economics particularly in Marx's writing. In conclusion he shows how these issues have a particular relevance in the present conjucture and in the postsocialist world.
Projekt MZOS
ENG